Efficacy of Ulinastatin in the Treatment of COVID-19: A Retrospective Study - Liu P; Wu Q; Li M (International Journal of General Medicine)
Peng Liu,1,2 Qi Wu,3 Mengjie Li2 1School of Graduate, Tianjin Medical University, Tianjin, People’s Republic of China; 2Department of Respiratory and Critical Care Medicine, Cangzhou Fifth Hospital (People’s Hospital of Qingxian), Cangzhou, People’s Republic of China; 3Department of Respiratory Medicine, General Hospital of Tianjin Medical University, Tianjin, People’s Republic of ChinaCorrespondence: Qi Wu, Department of Respiratory Medicine, General Hospital of Tianjin Medical University, Tianjin, People’s Republic of China, Email wuqitjykdxzyy@163.comPurpose: This retrospective study aimed to evaluate the efficacy of ulinastatin in the treatment of COVID-19 patients compared to conventional therapy.Patients and Methods: A total of 437 COVID-19 patients admitted to the Respiratory Oncology Department of our hospital between December 31, 2022, and July 8, 2023, were included in the study. Patients were classified into the observation group (n=62) receiving ulinastatin in addition to standard treatment and the control group (n=347) receiving standard treatment only. Clinical information, laboratory results, and treatment outcomes were collected and analyzed.Results: The observation group showed an improvement in lymphocyte count compared to the control group. The clinical improvement rate in patients receiving ulinastatin for 7 days or longer was 92.1%, significantly higher than that of patients treated for less than 7 days (62.5%) and those receiving standard treatment (71.0%). No significant difference in total length of hospitalization was observed between the two groups, and no related adverse events occurred in either group.Conclusion: Ulinastatin treatment improves lymphocyte counts in severe COVID-19 patients, and the clinical improvement rate is significantly higher with treatment duration of 7 days or longer. Larger-scale randomized controlled trials are warranted to further explore the role of ulinastatin in the management of COVID-19.Keywords: COVID-19, ulinastatin, severe cases, clinical improvement, radiographic findings